Monopolistic Behaviour, Prices and Quantities - Freixas, Xavier (Review of Economic Studies, 1980)
Journal Article Monopolistic Behaviour, Prices and Quantities Get access Xavier Freixas Xavier Freixas Université des Sciences Sociales, Toulouse Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 4, July 1980, Pages 747–753, https://doi.org/10.2307/2296940 Published: 01 July 1980 Article history Received: 01 September 1978 Accepted: 01 September 1979 Published: 01 July 1980